Transient effect of soil thermal diffusivity on performance of EATHE system. (November 2015) - Mathur, Anuj; Srivastava, Ayushman; Mathur, Jyotirmay; Mathur, Sanjay; Agrawal, G.D.
Abstract: This paper presents effect of thermo-physical properties of soil on performance of an Earth Air Tunnel Heat Exchanger (EATHE). The analysis has been carried out using a validated three-dimensional, transient numerical model for three different types of soil. The governing equations, based on the k – ε model and energy equation were used to describe the turbulence and heat transfer phenomena, are solved by using finite volume method. Comparisons were made in terms of temperature drop, heat transfer rate and COP of the EATHE system by operating it continuously for 12 h duration. The study reveals that each soil exhibits different rate of heat dissipation and thermal saturation over a period of continuous operation, which adversely affects the performance of EATHE. Dissipation of heat from the EATHE pipes to its surrounding soil and subsequently to the outer subsoil region is mainly found to be depending upon the thermal conductivity of soil; even of their thermal diffusivity is of different order.